2011
DOI: 10.1007/s00204-011-0651-z
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and ex vivo percutaneous absorption of [14C]-bisphenol A in rats: a possible extrapolation to human absorption?

Abstract: Bisphenol A (BPA) is a monomer used mainly in the synthesis of polycarbonates and epoxy resins. Percutaneous absorption is the second source of exposure, after inhalation, in the work environment. However, studies on this route of absorption are lacking or incomplete. In this study, percutaneous BPA absorption was measured in vivo and ex vivo in the rat, and ex vivo in humans. An approximately 12-fold difference in permeability between rat skin and human skin was found, with permeability being higher in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…BPA routinely leaches into the food and water supply from consumer products including food and liquid storage containers, baby bottles, and linings of aluminum cans. While the main route of human exposure to BPA is through indigestion of contaminated food and water, possible exposure through inhalation and dermal routes may exist due to the presence of BPA in dental sealants and thermal paper (Vandenberg et al, 2007; Marquet et al, 2011). Human exposure to BPA is widespread with National Health and Nutrition Examination Survey (NHANES) data revealing detectable amounts of BPA in the urine of 95% of study participants (Calafat et al, 2005; Vandenberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…BPA routinely leaches into the food and water supply from consumer products including food and liquid storage containers, baby bottles, and linings of aluminum cans. While the main route of human exposure to BPA is through indigestion of contaminated food and water, possible exposure through inhalation and dermal routes may exist due to the presence of BPA in dental sealants and thermal paper (Vandenberg et al, 2007; Marquet et al, 2011). Human exposure to BPA is widespread with National Health and Nutrition Examination Survey (NHANES) data revealing detectable amounts of BPA in the urine of 95% of study participants (Calafat et al, 2005; Vandenberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo and in vivo percutaneous absorption fluxes of BPA after 24 hour exposure in the rat were in the same range (1.48 and 2.2 μg/cm 2 /h) (Marquet et al, 2011). They found approximately 12-fold lower flux (0.12 ± 0.09 µg/cm 2 /h) in human skin samples treated in vitro in the same conditions ( 14 C-BPA in acetone: 4 mg BPA/mL; 50 and 200µl/cm 2 for human), however, inter-and intra-individual variability of up to tenfold was observed.…”
Section: Dermal Absorptionmentioning
confidence: 68%
“…The half-life of BPA after dermal absorption was estimated to be 28 h (compared with the half-life of 10 h measured after i.v. administration in the same study) (Marquet et al, 2011). When dermal absorption was measured ex vivo in human and rat skin at the studied dose, BPA was not cytotoxic for the skin and did not affect the skin's integrity.…”
Section: Dermal Absorptionmentioning
confidence: 83%
“…Studies of human skin explants to assess skin penetration of BPA have observed that~9.5-33% of the applied dose is transferred through the skin as free BPA within 24-48 h of topical application. [84][85][86] However, it is uncertain how these finding relate to living tissue, in particular in young children. The skin of human neonates is immature at birth and takes at least 3-5 months to attain similar barrier properties as those of adults.…”
Section: Non-dietary Exposure Sources May Have Multiple Exposure Routesmentioning
confidence: 99%